Knowledge and skill among lecturers in community college: case study - Liu, Tse Hui. (Universiti Malaysia Sarawak (UNIMAS), 2013)
Qualifications of skilled workers in the field of technical and vocational education are key issues for the competitiveness of the economy in most countries in the world. therefore, the knowledge and skill of lecturers in technical and vocational education training (TVET) Malaysia should be emphasized to ensure that quality employees can achieve competitive excellence in the international competition level. This study is to explore knowledge and skill among TVET lecturers in one of community colleges in Sarawak.